Influence of salt of different origin on the microbiological characteristics, histamine generation and volatile profile of salted anchovies (Engraulis encrasicolus L.). (October 2018) - Alfonzo, Antonio; Gaglio, Raimondo; Francesca, Nicola; Barbera, Marcella; Saiano, Filippo; Santulli, Andrea; Matraxia, Michele; Rallo, Francesco; Moschetti, Giancarlo
Abstract: The effect of six salts of different geographical areas on the quality of salted anchovies was evaluated. The crude salts were chemically characterized by determination of inorganic and volatile organic compounds (VOCs). Salted anchovies, corresponding to six experimental trials, were subjected to microbiological, chemical (including histamine content) and sensory analysis during the entire period of ripening (150 days). The salts were characterized by marked differences in terms of major cations and trace element amounts. Among the 27 VOCs detected, octadecane was the most abundant compound and the main differences of the salts were registered for alkanes and alcohols. During maturation, significant microbiological differences between the salts were found for the levels of total aerobic mesophilic microorganisms, lactic acid bacteria, Staphylococcaceae and Enterobacteriaceae counts. All salted anchovies contained histamine below the thresholds allowed by current regulations, but statistical differences were registered for the concentrations of the different trials. Consistent differences were also revealed for their sensory profiles, in particular concerning odour and taste and overall acceptability. Several differences were also detected for dryness, brown colour, putrid odour, rancid and raw blood taste sensory attributes. Especially the differences in the composition (chemical and VOC's) of the raw salts used for the production of salted anchovies has a significant effect on the sensory characteristics of the final product. Highlights: Histamine levels are related to the type of salt used in salting process. Geographic origin of salts influences the characteristics of salted anchovies. VOC profiles of raw salts were different in relation to their geographical origin.